PENGARUH METODE BERMAIN PERAN TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SD INPRES 12/79 BIRU II KECAMATAN TANETE RIATTANG KABUPATEN BONE - Abd. Hafid,; Sudarto, Sudarto; Muh. Afri Zulfahmi, (Jurnal Cakrawala Ilmiah, 2024)
This research is a pre-experimental research which aims to find out whether the Role Playing method can or cannot improve the speaking skills of the 5th Grade students at SD Inpres 12/79 Biru II Biru, Tanete Riattang District, Bone Regency. The subjects of this research were the students from class the 5th Grade SD Inpres 12/79 Biru II, Tanete Riattang District, Bone Regency, in amount of 23 people. The data collection technique used was a test technique and the data analysis technique was a quantitative descriptive and inferential techniques. Research results: tcount = 13.480 and ttable = 2.074 where tcount > ttable (there was a significant difference between speaking skills before and after using the role playing method), pretest average = 61.22 and posttest average = 86.74 (the posttest average is higher than the pretest average). Conclusion: the role playing method has a significant effect to improving the speaking skills of fifth grade students at SD Inpres 12/79 Biru II, Tanete Riattang District, Bone Regency